Pyridoxine-dependent seizures - Ulvi, H; Müngen, B; Yakinci, C; Yoldas, T (Oxford Univ Press, 2002)
Pyridoxine-dependency is a rare autosomal recessive disorder causing a severe seizure disorder of neonatal onset. There are a few reports including neuroimaging studies, such as cranial CT and MRI, and one report with longitudinal MRI findings in two cases with pyridoxine-dependent seizures (PDS). We report long-term follow-up of two siblings with PDS in the light of clinical, EEG, CT and MRI findings, and pyridoxine treatment. The first patient, an 8-year-old female who had neonatal seizures, has sequential cranial CT and MRIs which are normal except for mega cistema magna thus far. She still has mild mental retardation, although the accurate diagnosis was made when she was 6 years old and pyridoxine treatment was initiated. The second patient, a 1-year-old female, who is the younger sibling of the first patient, presented with neonatal seizures and PDS was diagnosed immediately, with resulting pyridoxine treatment (10 mg/kg/day). She is now neurologically normal, seizurefree, and has sequential normal CT and MRIs. These patients show rather benign clinical courses.
Keywords: Brain; Glutamate; Epilepsy; Disease; Eeg